Pengaruh Digital Marketing dan Promosi Penjualan terhadap Keputusan Pembelian pada TWN Second Store Tasikmalaya - Tisna Romadoni; Hartanto Halim; Eman Sulaiman (Yayasan Literasi Sains Indonesia, 2024)
This study aims to determine: (1) the influence of digital marketing on purchasing decisions at TWN Second Store Tasikmalaya, (2) The influence of sales promotion on purchasing decisions at TWN Second Store Tasikmalaya. The type of research used is quantitative research. The population in this study were consumers of TWN Second Store Tasikmalaya totaling 900 people. The sampling technique used purposive sampling with a sample size of 90 people. This data collection technique uses a questionnaire that has been tested for validity and reliability. The analysis technique used in testing the hypothesis is the multiple linear regression analysis technique. The results of the study show that: (1) Digital marketing has a positive effect on purchasing decisions at the TWN Second Store Tasikmalaya of 82.6% and is proven by a sign value of 0.000<0.05, and the regression coefficient has a positive value of 0.448. (2) Sales promotion has a positive effect on purchasing decisions at the TWN Second Store Tasikmalaya of 74,0% and is proven by a sign value of 0.001<0.05, and the regression coefficient has a positive value of 0.279. (3) Digital marketing and sales promotions have a positive value and have a simultaneous influence on purchasing decisions at TWN Second Store of 84.4% and are proven by a sign value of 0.000<0.05.